Nomenclatural notes on Melastomateae (Melastomataceae) - Guimarães, Paulo José Fernandes; Michelangeli, Fabián A. (Phytotaxa, 2021)
The purpose of this correspondence is to add, correct, or clarify some nomenclatural and taxonomic issues in the tribe Melastomeae Bartling (1830: 329), mostly due to recent changes in the taxonomy of the large genus Tibouchina Aublet (1775: 445). Recently a new taxonomic framework for Tibouchina was presented by Guimarães et al. (2019), in which taxa in this large genus were rearranged in four genera: Tibouchina, the newly erected Andesanthus P.J.F.Guim. & Michelang. in Guimarães et al. (2019: 947–948), and the resurrected Chaetogastra Candolle (1828: 131) and Pleroma Don (1823: 283). In this work (Guimarães et al. 2019) three species were omitted, and two others wrongly transferred, and those issues are corrected here.